Market Structure and Performance of Commercial Banks: Empirical Evidence from Nepal - Kunwar, Kripa (Journal of Business and Management, 2018)
The study attempts to examine the relationship of market structure variable with the performance of Nepalese commercial banks over the period 2011-2015 using causal research design. The stratified sampling technique has been employed to select sample banks which include 10 commercial banks comprising 5 joint venture and 5 local private banks. A pooled OLS model is specified, and then the indicators of market structure are used as explanatory variables in the regression model. Study results have shown that market concentration has had a negative and significant impact on the performance of the Nepalese commercial banks. Where the Herfindahl-Hirschman index (HHI) is used the market shares as the main variable to measure the concentration (CONC). Empirical results revealed that lower the market concentration higher will be the performance of the bank. On the other hand, study concluded that market power has positive influence on profitability. The Data Envelopment Analysis (DEA) method was used to assess the efficiency scores. On the contrary, empirical results indicated that there is no relationship between the bank’s efficiency and performance in Nepalese commercial banks. As far as the ownership structure is concerned, study found that, ROA differences depend on bank ownership types. Study concluded that performance of the joint venture banks is better than local private banks in sample period.